Natural history and quality of life in patients with cystine urolithiasis: a single centre study. (21st July 2015) - Parr, Justin M.; Desai, Devang; Winkle, David
Abstract : Objective: To describe the natural history and quality of life (QoL) in patients with cystine urolithiasis. Patients and Methods: A cohort study was carried out involving participants recruited from a single surgeon's case mix. Patients with cystinuria and related urolithiasis were invited to complete a questionnaire involving demographic information, use of medical treatment, surgical interventions and the 36‐item short‐form 36‐item short‐form health survey (SF‐36). Results: In all, 14 patients completed the survey. The SF‐36 survey showed lower QoL than the general public in seven of eight domains. The mean interventional rate in patients with cystinuria was 10.6 procedures per patient. Most patients reported previous use ofd ‐penicillamine and urinary alkalinisation medications, with most ceasing due to side‐effects or lack of perceived efficacy. Conclusion: Cystinuria is associated with a high rate of surgical intervention and lower QoL than the general public. Individuals with this condition report that medical management is either ineffective or poorly tolerated. There is a need for further improvements in medical management of cystinuria, to reduce the rate of operative intervention.